THE ROLE OF INTERNATIONAL MONETARY FUND (IMF) IN ECONOMIC RECOVERY DURING ECONOMIC CRISIS OF INDONESIA - Lena Farsia (Universitas Syiah Kuala, 2021)
The International Monetary Fund (IMF) has a primary role in providing financial support to countries facing financial crises, such as the 1998 world financial crisis. The situation has brought an enormous impact on developing countries, particularly Indonesia. This paper explores the role of The IMF and maps out the problems related to the financial crisis and its impact on Indonesian political reforms. It will be done by compiling the milestones in chronological order from 1997 until 2017. It also aims to examine the lending policies of the International Monetary Fund, which brings a country like Indonesia becomes addicted and difficult to survive or improve in its economic development. There will be an understanding of how the actual process happens. It can be used as an instrument to assess whether the existence and role of the IMF in Indonesia have a better or harmful impact on the long-term economic development of Indonesia. Keywords: The International Monetary Fund (IMF), Economic Development, Financial Crisis